PENDEKATAN PSIKOLOGI TERHADAP ADIKSI - Patriana Patriana (Al-SAMBASY: Jurnal Kajian Pendidikan, 2025)
Addiction is a psychological disorder marked by reliance on a drug or behaviour that yields transient pleasure but results in detrimental long-term consequences. Addiction exerts profound and extensive impacts on individuals, families, and society at large, necessitating intervention. Addiction can adversely affect an individual's physical and mental well-being, diminish productivity, and impair social and emotional functioning. This study aims to elucidate psychological methodologies, including cognitive, behaviouristic, psychoanalytic, and biological techniques, employed in the treatment of addiction. This study employs a literature review methodology.